The validity of Bradford’s Law in academic electronic mailing lists - Faba-Pérez, Cristina; Cordero-González, Ana-María (Electronic library, 2015)
Purpose – The purpose of this paper was to check the validity of Bradford’s Law in the contemporary world of academic electronic mailing lists. Design/methodology/approach – The present research study applied Bradford’s Law to academic electronic mailing lists to determine: whether, on the Internet, mailing lists and the posts sent to them follow the same distribution as scientific journals and the articles published in them with respect to the original form of Bradford’s Law; and whether the behaviour of the Bradford distributions differs depending on the type of academic discipline (social studies or sciences) and subject category (documentation and education, medicine and life sciences) to which the list belongs. As a prior step, the utility of mailing lists was analysed during the 10-year period of 2002-2011, together with their expected future in terms of ratifying the applicability of the Law. Findings – The results showed that, in general, electronic mailing lists are continuing to be used, and that Bradford’s Law is indeed satisfied, especially in the science subject categories, coherent with the fact that Bradford’s Law in cybermetrics holds only for fairly narrow (closed) and well-defined (homogeneous) environments. Originality/value – The originality of the present research study was to check the validity of the historic Bradford’s Law in the contemporary world of Internet.